On the Efficiency of Capacitively Loaded Frequency Reconfigurable Antennas - Samantha Caporal Del Barrio; Gert F. Pedersen (International Journal of Distributed Sensor Networks)
The design of a reconfigurable antenna that can be fine tuned to address future communication systems is proposed. The design consists of a capacitively loaded patch antenna for nowadays smartphone platforms. The antenna is narrowband and can be fine tuned over the range (700 MHz–960 MHz). Measurements at 700 MHz with fixed capacitors raise the challenge of the component insertion loss. Distribution of the tuning capacitance is investigated and shows 1 dB improvement in the antenna radiation efficiency.